The anatomy of dance discourse literary and philosophical approaches to dance in the later Graeco-Roman world - Schlapbach, Karin 1969- (Oxford, United Kingdom Oxford University Press, 2018)
The Anatomy of Dance Discourse offers a fresh, original perspective on ancient perceptions of dance. Focusing on the second century CE, it provides an overview of the dance discourse of this period, juxtaposing philosophical and literary conceptualizations of dance and exploring how they interacted with different areas of cultural expression.
Includes bibliographical references (pages [289]-328) and index.
Keywords: Civilization, Graeco-Roman.; Dance -- Rome -- History .; Dance -- Anthropological aspects -- Rome